PENGARUH VARIASI KONSENTRASI HPMC SEBAGAI GELLING AGENT TERHADAP SIFAT FISIK GEL ANTINYAMUK DAUN KENIKIR (Tagetes erecta L.) - Mikhania C.E., Asa Falahi, Dewi Ratna Sari (AKADEMI FARMASI JEMBER, 2019)
The aim of this research was to understand the influence of HPMC variation concentration to the physical characteristic anti mosquito gel of extract kenikir leaves (Tagetes erecta L.). Pre-experiment the one shot case study was used as the research design. The variation of HPMC concentration were 2%; 2,5% and 3%. The materials used in this research were kenikir leaves extract, propylenglycol, methyl paraben, jasmine oil and aquadest. The result show that the variation concentration of HPMC give influence to physical properties of organoleptic gel (form, colour), pH and viscosity. The variation concentration of HPMC did not influence homogeneity, spreadibility and smell of the gel.Keywords : Kenikir leaves, HPMC, Anti Mosquito Gel.